EMPOWERING ACCOUNTING EDUCATION: A STUDY ON MICROSOFT EXCEL KNOWLEDGE AND SKILLS - Safa Saif Alobaidani; Maitha Fahad Albattasi; Mohammed Muneerali Thottoli (International Journal of Innovative Technologies in Social Science, 2023)
Purpose- The aim of this research is to know the level of Microsoft (MS) excel knowledge and skills in the broad field of accounting education. Design/methodology/approach- The survey questionnaire is designed as a research instrument and distributed to graduate students enrolled in an accounting course from Oman universities. 142 questionnaires were gathered using Google Forms and analyzed using the partial least-squares structural equations modeling (PLS-SEM) technique. Findings- The findings show that both MS Excel knowledge and skills are most important and developing MS excel skills in accounting education suggest that the Omani accounting education system might do more to give opportunity for students to thrive in their future careers. Research limitations/implications- The findings provide MS knowledge and skills of accounting graduates in Oman’s higher educational institutions (HEIs). In particular, this study sheds light on the skills that accounting students want and how relevant these skills for Omani graduates. Practical Implications- Some modifications to accounting education are proposed to enhance accounting students’ MS skills. Originality/value- Because there is a lack of specific research on MS excel knowledge and skills in accounting education in Gulf Cooperation Council (GCC) countries, this study contributes to the body of expertise on MS skills in GCC countries, especially in Oman.